Determinants of continuance intention Flip applications by millennial generation - Annisa Chairani; Ignatius Heruwasto (President University, 2022)
The progress of fintech affects human lifestyles, especially young people. Fintech is developing in parallel with people's lifestyle changes, which are currently dominated by information technology users with fast-paced life demands. In Indonesia, at this time, users of interbank transfer services will be charged a tariff of 6500 rupiahs. Flip is an application that allows users to make inter-bank transfers at no cost. However, research that examines the determinants of continuance intention in Flip applications usage is still limited. This study's purpose is to the determinant factors which influence continuance intention towards Flip application usage by the millennial generation. This research employs Structural Equation Modelling (SEM) with 100 millennial respondents living in Greater Jakarta (Jabodetabek). This study found that the factors of attitude, subjective norms and perceived behavioral control had a positive and significant effect on fintech continuance intention in using the Flip application. These factors together affect continued intention towards Flip application usage. This study highlights the important factors that influence people to use fintech continuously. This study would be insightful for fintech companies in planning their strategies to encourage customers to use fintech services. The fintech company should improve the system's quality and design to be aligned with people's habits so that they can be agents to promote the fintech services as well.